Prevalence of Xenopsylla cheopis in Rattus rattus in the Salas district, Lambayeque ... : انتشار Xenopsylla cheopis في Rattus rattus في منطقة Salas، Lambayeque ... - Jarling F. Ortiz-Cusma; Kattya M. Martínez-Bravo; Sebastián Iglesias-Osores (OpenAlex, 2022)
Objective: The study of the prevalence of Xenopsylla cheopis in rodents of the Rattus rattus species.The objective of the present investigation is to establish the prevalence of Xenopsylla cheopis in rodents of the Rattus rattus species. Methods: To obtain the sample, Tomahawk and Sherman traps were used that contained baits previously prepared with oatmeal and vanilla, the traps were placed in three areas: intra-home area, peridomyciliary area and in the open area. Ectoparasites were obtained using the fine comb technique. With an entomological clamp, fleas were collected in a 2ml vial, containing 70% alcohol. Results: Its prevalence in Rattus rattus rodents were evaluated, with the highest prevalence rate being the one registered in the locality of Banco in August 2016 (4.08) and the lowest index was 1.3 registered in the locality of the Ramada in November 2015. They were captured 169 rodents Rattus rattus, of which 399 fleas could be collected, 299 belonged to the Xenopsylla cheopis species. Conclusion: ... : الهدف: دراسة انتشار Xenopsylla cheopis في القوارض من نوع Rattus rattus. الهدف من هذا التحقيق هو تحديد انتشار Xenopsylla cheopis في القوارض من نوع Rattus rattus. الطرق: للحصول على العينة، تم استخدام مصائد توماهوك وشيرمان التي تحتوي على الطعوم التي تم تحضيرها مسبقًا مع دقيق الشوفان والفانيليا، وتم وضع المصائد في ثلاث مناطق: المنطقة داخل المنزل، والمنطقة المحيطة بالفطريات وفي المنطقة المفتوحة. تم الحصول على الطفيليات الخارجية باستخدام تقنية المشط الدقيق. باستخدام مشبك حشري، تم جمع البراغيث في قنينة سعة 2 مل، تحتوي على 70 ٪ من الكحول. النتائج: تم تقييم انتشاره في قوارض راتوس راتوس، حيث كان أعلى معدل انتشار هو المعدل المسجل في منطقة بانكو في أغسطس 2016 (4.08) وكان أدنى مؤشر 1.3 مسجل في منطقة رامادا في نوفمبر 2015. تم القبض عليهم 169 من القوارض راتوس راتوس، منها 399 من البراغيث التي يمكن جمعها، 299 تنتمي إلى أنواع Xenopsylla cheopis. الخلاصة: وجد أن انتشار Xenopsylla cheopis في قوارض راتوس راتوس في مواقع Sauce و Banco و Kerguer و Algarrobo و Ramada في منطقة Salas، في الفترة من يوليو إلى نوفمبر 2015 وأغسطس 2016 كان ...